Discussion Method and Critical Thinking Growth in Elementary IPAS: Metode Diskusi dan Pertumbuhan Pemikiran Kritis dalam Pendidikan Dasar IPAS - Voni Andriyani; Enik Setiyawati (Universitas Muhammadiyah Sidoarjo, 2025)
This study addresses the development of higher-order thinking skills in primary education within the context of 21st-century learning demands. General Background: Critical thinking is recognized as a core competency required to respond to global educational challenges and to support meaningful learning in science and social science subjects. Specific Background: In Indonesian elementary classrooms, learning practices often remain teacher-centered, limiting students’ opportunities to actively analyze, argue, and construct knowledge in IPAS subjects. Knowledge Gap: Empirical evidence at the elementary level regarding structured discussion methods and measurable critical thinking indicators in IPAS remains limited, particularly using quantitative pre-experimental design. Aims: This study aimed to measure changes in students’ critical thinking skills after the implementation of the discussion method. Results: Using a one-group pretest-posttest design involving 23 fifth-grade students, statistical analysis through paired sample t-test showed a significance value of 0.000 < 0.05, indicating a meaningful difference between pretest and posttest scores across five critical thinking indicators. Novelty: The study integrates structured discussion syntax with measurable critical thinking components in IPAS learning at the elementary level. Implications: The findings support discussion-based active learning as a practical classroom strategy to foster analytical reasoning, student participation, and 21st-century competencies in primary education. Keywords: Discussion Method, Critical Thinking Skills, IPAS Learning, Elementary Education, Active Learning Key Findings Highlights: Statistical testing revealed a meaningful difference between initial and final assessment scores. All five measured reasoning indicators showed measurable progression after treatment. Classroom dialogue procedures supported student participation and analytical engagement.